The ‘Lunar Side’ of the story: exploring the sustainability of curricular internships in higher education - Lopes, Betina (2019)
Curricular internships are increasingly seen as an effective strategy capable of contributing to the objectives and targets of the sustainable development paradigm, both in its social, economic and institutional dimensions. This positive outlook is ingrained within the large bulk of existing research, which has been focused on the discussion of positive outputs, such as the enhancement of graduates′ competences (employability) and their work integration (employment). An important, albeit relatively unexplored, feature of the sustainable institutional politics of curricular internship management pertains to the assessment of its associated liabilities and tensions. This article seeks to address this challenge, by analyzing two interrelated dimensions. First, it seeks to understand the internship processes ranging from the planning to the implementation stages. Second, it elicits the associated negative aspects (the ‘lunar side’) of internships, allowing for an assessment of the features where there is room for improvement. Empirically, this article draws on in‐depth qualitative research. It presents the results of four focus groups, voicing the perceptions of top management structures and students involving first cycle degrees in the areas of Marketing, Management, and Accounting from four public Portuguese Higher Education Institutions (HEIs)‐three polytechnics and one university. Findings confirm the general positive outlook of internships. Perceived negative perspectives report to both internal problems (such as the lack of institutional support and curricular design) and external problems (e.g., the shortage of suitable internship placements), constituting barriers towards sustainable institutional policies and strategies. Adaptive strategies to overcome specific difficulties are highlighted (e.g., establishment of advisory committees with local businessmen). Finally, recommendations regarding curricular internship management at HEIs are delineated (e.g., investment in monitoring and evaluation strategies of internships).